PERANAN TRICHODERMA SEBAGAI AGEN PENGENDALI HAYATI DAN BIOKOMPOS PADA TANAMAN GOLDEN MELON DI DESA AGROWISATA KEBON AYU KECAMATAN GERUNG KABUPATEN LOMBOK BARAT: The Function Of Trichoderma As A Biocompost And Biocompost Agent In Gold Melon Plants In Kebon Ayu Agrotourism Village, Gerung District, West Lombok Regency - Apzani, Wawan; Haryantini, Baiq Azizah; Sunantra, I Made; Wardhana, Agung Widya; Arifin, Zainal; Baharuddin, Baharuddin; Zainab, Siti (Yayasan Al-Amin Qalbu, 2023)
Agrotourism is an activity that utilizes the agricultural sector for tourism in order to attract the interest of visitors so that it can increase the economic value of the community both in terms of scenery, agricultural activities and technology. Kebon Ayu Village currently has golden melon agrotourism which is very popular with tourists. However, the problem of expensive fertilizer prices and pest and disease attacks are obstacles to plant growth and development. One of the diseases that appears is powdery mildew. This disease is caused by the fungus Podosphaera xanthii which is transmitted through the wind. Therefore, this community service activity is carried out to help farmers minimize disease attacks on melon plants and to help farmers use animal waste into biocompost fertilizer. An alternative method is to use the Trichoderma spp. fungus as a biological control agent. It is hoped that the use of this fungus will be useful as a preventive measure to prevent powdery mildew disease on golden melon plants in the Kebon Ayu Agrotourism village